Paparan Particulate Matter (PM10) Terhadap Keluhan Subjektif Infeksi Saluran Pernapasan Akut (ISPA) Pada Pekerja Kapal Phinisi Di Kabupaten Bulukumba - Kahfi, Muh; Rahmah, Nur; Suryadi, Iwan (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Air pollution is a serious global public health problem, contributing significantly to various respiratory diseases, including acute respiratory infections (ISPA). One of the hazardous components of pollution is small particles called PM10. PM10 has a profound impact on respiratory health, as long-term exposure to PM10 can increase the risk of respiratory disorders, especially among workers exposed to polluted environments. This study aims to analyze the effect of PM10 exposure on subjective complaints of ISPA in Phinisi ship workers in Tanah Lemo Village, Bonto Bahari District, Bulukumba Regency. The research method used is quantitative research with an analytical observational design and a cross-sectional approach. The population in this study comprised all Phinisi ship workers. The sample was determined using a purposive sampling technique of 127 based on the established inclusion criteria; however, only 41 respondents were willing to participate. Data were collected through structured interviews and PM10 concentration measurements using the Hazard-Dust EPAM 5000 device. The results showed that PM10 concentrations at the Phinisi shipbuilding site exceeded the established threshold, with an average concentration reaching 126 mg/m³. Bivariate analysis showed a significant relationship between PM10 exposure and subjective complaints of ISPA (p-value <0.05), as well as between individual characteristics—such as smoking status and the use of personal protective equipment (PPE) and ISPA complaints. These findings indicate that workers exposed to PM10 for a long period have a higher risk of experiencing ARI complaints. The results of this study are expected to provide significant contributions to the development of occupational health and safety policies, as well as recommendations for improving ventilation and using more effective PPE in the shipbuilding industry. Thus, appropriate preventive measures can be implemented to protect the health of workers in the maritime sector